Climate change shapes the future evolution of plant metabolism. Issue 1 (10th August 2020) - Xu, Sophia Y.; Weng, Jing‐Ke
Abstract: Planet Earth has experienced many dramatic atmospheric and climatic changes throughout its 4.5‐billion‐year history that have profoundly impacted the evolution of life as we know it. Photosynthetic organisms, and specifically plants, have played a paramount role in shaping the Earth's atmosphere through oxygen production and carbon sequestration. In turn, the diversity of plants has been shaped by historical atmospheric and climatic changes: plants rose to this challenge by evolving new developmental and metabolic traits. These adaptive traits help plants to thrive in diverse growth conditions, while benefiting humanity through the production of food, raw materials, and medicines. However, the current rapid rate of climate change caused by human activities presents unprecedented new challenges to the future of plants. Here, we discuss the potential effects of modern climate change on plants, with specific attention to plant specialized metabolism. We explore potential avenues of future scientific investigations, powered by cutting‐edge methods such as synthetic biology and genome engineering, to better understand and mitigate the consequences of rapid climate change on plant fitness and plant usage by humans. Abstract :